Pulsed field, PCR ribotyping and multiplex PCR analysis of Yersinia enterocolitica strains isolated from meat food in San Luis Argentina - Lucero Estrada, Cecilia Stella Marys (2011)
The characterization of phenotypic and genotypic virulence markers of Yersinia enterocolitica strains belonging to biotypes (B) 1A, 2 and 3, mostly isolated from food in San Luis, Argentina, and the assessment of their genotypic diversity using PFGE and PCR ribotyping, were performed in our laboratory for the first time. Thirty five Y. enterocolitica strains, two reference strains and 33 strains isolated in our laboratory were studied. The presence of virF, ail, ystA, and myfA genes was investigated by multiplex PCR. The pathogenic potential of B1A strains, the most predominant biotype of Y. enterocolitica strains isolated from meat in our region, was investigated by simple PCR. Four B1A strains were positive for ystB gene. Four Y. enterocolitica 2/O:9 (bio/serotype) and two 3/O:5 strains isolated in our laboratory showed virulence-related results in the phenotypic tests and multiplex PCR. A good correlation between the expression of virulence markers and their corresponding genotypes was observed for most strains. Sixteen genomic types (GT) and 9 different intergenic spacer region (SR) groups were generated by PFGE and PCR ribotyping, respectively. In both cases the Y. enterocolitica 2/O:9 strains were separately clustered from 1A and 3/O:5 strains. Meat foods might be vehicles of transmission of pathogenic Y. enterocolitica strains in our region.